PENGARUH BEBAN KERJA, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PARAMEDIS DI RUMAH SAKIT ISLAM GARAM (RSIG) KALIANGET KABUPATEN SUMENEP - Millatul Kamilah; Dina Kurniawati (Journal MISSY (Management and Business Strategy), 2020)
The problem that will be discussed in this research is the influence of workload, compensation, and work environment on the performance of paramedic employees in kalianget salt hospital (RSIG), sumenep regency. Where the purpose of the problem can be known how much influence the workload, compensation, and work environment on the performance of paramedical employees in the kalianget salt islamic hospital (RSIG) in sumenep regency, both partially and simultaneously. In answering these problems, quantitative methods are used as a type research. 67 respondents were known with this analysis of sampling using no-prpbability sampling with data collection techniques using purposive sampling. The results of this study indicate that partially the workload, compensation and work environment variables affect employee performance. And simultaneously the workload, compensation and work environment variables influence employee performance.